2013
DOI: 10.1007/s11144-013-0628-4
|View full text |Cite
|
Sign up to set email alerts
|

A deactivation mechanism of sulfated titania in the esterification of acetic acid and n-butanol

Abstract: The present work systematically investigated the deactivation of sulfated titania in the esterification of acetic acid and n-butanol. Under the set conditions, sulfated titania was used 20 times and for 10 h accumulatively. The catalyst had the largest catalytic activity of 95.69 % at the second cycle and then the catalytic activities gradually dropped, and the last-cycle conversion of acetic acid was 46.15 %, suggesting a serious deactivation of the catalyst of sulfated titania after use in 20 cycles. XPS, FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Moreover, this class of catalysts can simply be retrieved and recycled, which classify these reactions as some of the green synthetic methodologies [2]. Amongst the abundant solid catalysts, sulfated metal oxides received more attention in recent years as potential catalysts for numerous reactions [3]. In comparison to acidic liquid catalysts, solid catalysts were found 2 of 18 to be less corrosive and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this class of catalysts can simply be retrieved and recycled, which classify these reactions as some of the green synthetic methodologies [2]. Amongst the abundant solid catalysts, sulfated metal oxides received more attention in recent years as potential catalysts for numerous reactions [3]. In comparison to acidic liquid catalysts, solid catalysts were found 2 of 18 to be less corrosive and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic routes were applied for the preparation of heterogeneous catalysts including sol-gel [24][25][26][27], solvent-free [28,29] and hydrothermal methods [30][31][32][33]. Examples of heterogeneous catalysts include SO /TiO2 [30,[34][35][36][37],, SO /TiO2-SiO2 [38][39][40][41], SrO/SO -ZrO2 [29], SO /ZrO2 [17,[42][43][44], SO /TiO2-ZrO2 [45] and SO /SnO2 [17,46], which were considered for a good catalytic activity for the raw materials containing large amounts of FFA in biodiesel production. Among these, sulphated doped TiO2 is a good example of a solid super-acidic catalyst which is also used in the petrochemical industry and petroleum refining process [24,47] and showed better performances as compared to other sulphated metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that the addition of sulphate ions to metal oxides enhances the acidic properties, catalytic activity, high selectivity, and causes less deactivation of the catalyst [25,[53][54][55][56]. However, Shi and Li [36] observed the deposition of carbon on the surface of sulphated metal oxide catalysts is the main reason to poison the catalytic activity of sulphated titania.…”
Section: Introductionmentioning
confidence: 99%